Korean Poetic Form “Sijo” - Ş. Yeşim FERENDECİ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
Sijo is representative of Choson period poetry. Its poetic form was established in late Koryo period, but flourished to a greater extent under Choson period. The form of sijo applies only to the standard form called plain sijo or p’yong sijo. The other two forms are called medium or oss sijo which is expanded in syllabic count, most often in the first phrase-grouping or the second in the first line and sometimes in the last or middle line, adding two or three more phrase-groups to standard form. And long sijo or sasol sijo, retaining three line structure, is almost formless, expanded in every line and mostly in the middle into hundreds of syllables. Sijo is, first and foremost, a song. Sijo was sung or chanted with musical accompaniment, and this tradition survives. The word originally referred only to the music, but it has come to be identified with the lyrics.